Fixed in time and "time in motion": Mobility of vision through a SenseCam lens - Lindley, Siân; Harper, Richard; Randall, Dave; Glancy, Maxine; Smyth, Nicola (Proceedings of the 11th international conference on Human-Computer Interaction with Mobile Devices and Services, 2009)
SenseCam is an automatic wearable camera, often seen as a tool for the creation of digital memories. In this paper, we report findings from a field trial in which SenseCams were worn by household members over the course of a week. In interviews with these users, it became apparent that the way in which SenseCam images were played back, the manner of which might be described as a stilted movie, affected the values that were realised within them. The time-lapse nature of the image stream led participants to romanticise the mundane and find sentimentality in unexpected places, and was particularly effective at portraying personality and play. In so doing, SenseCam images enlivened the visual recording of everyday scenes. These values influenced what the participants sought to capture and view, and have implications for technologies that might support lifelogging or the development of user-generated content.